The Intricate Dynamics of Democratic Crises in Least Developed Countries - Thapa, Santa Bahadur (Darul Yasin Al Sys, 2025)
This paper explores how the economic crisis, lack of education, political corruption, and Western intervention contribute to declines in overall democratization in developing or LDC nations. Using a comparative analysis of case studies from various regions, the study analyzes cross-cutting trends and deviations in democratic backsliding. This paper suggests how economic instability either originates in or feeds resource scarcity and instability in local and world markets, resulting in a downward spiral of poverty, unemployment, and social unrest that can destroy public confidence in democratic institutions. Keeping the access to education to the masses low, with the representatives disengaging from their voters, makes the individuals vulnerable and weak, making democracy weak. One example is political corruption, which abuses power for personal gain, undermining public trust and confidence in democratic governance. The trajectory where this was at that point could be influenced by external actors, like foreign aid or structural adjustment programs from international financial institutions, that perpetuate dependency and, if the terms of those loans are not met, impose austerity packages that shrink democracy. This paper contributes to the academic literature on LDCs challenged by crisis redeems in democracies by highlighting processes over multiple years that determine crises as the formation of social, economic, political, or external tensions involving three interconnected levels of operations of tensions: social, economic, and political; political and external; and financial and external. Such insights illustrate the urgency for holistic solutions that confront the causes of democratic deterioration and enable the US to build sustained support that is successful against those most at risk.